2016
DOI: 10.13005/ojc/320210
|View full text |Cite
|
Sign up to set email alerts
|

Reverse docking study unravels the potential Mycobacterium tuberculosis enzyme targets of Agelasine F

Abstract: The natural product Agelasine F found in marine sponge Agelas sp. along with the known inhibitors of the target enzymes in Mycobacterium tuberculosis (Mtb), and the first-line tuberculosis (TB) drugs have been docked to enoyl reductase (InhA), Isoniazid-resistant I21V and S94A enoyl-ACP (COA) reductase mutant enzymes, 7,8-diaminopelargonic acid synthase (DAPAS), pantothenate synthetase (PS), and lipoate-protein ligase B (LipB) enzymes. Among the compounds studied, Agelasine F came out as the best inhibitor for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…[70][71][72][73][74][75][76] Reverse or inverse molecular docking helps in determining the probable protein targets of a ligand and shed some light on the possible mechanism of action of a drug. 47,48 In this study, reverse docking was conducted to investigate the interaction between syringin and various angiogenesis-related proteins at the molecular level, particularly examining the hydrogen bonds, van der Waals and hydrophobic interactions, which are the principal driving force in maintaining a stable ligand-protein complex. 77…”
Section: Reverse Molecular Docking Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…[70][71][72][73][74][75][76] Reverse or inverse molecular docking helps in determining the probable protein targets of a ligand and shed some light on the possible mechanism of action of a drug. 47,48 In this study, reverse docking was conducted to investigate the interaction between syringin and various angiogenesis-related proteins at the molecular level, particularly examining the hydrogen bonds, van der Waals and hydrophobic interactions, which are the principal driving force in maintaining a stable ligand-protein complex. 77…”
Section: Reverse Molecular Docking Analysismentioning
confidence: 99%
“…In this work, reverse molecular docking technique 47 , 48 was conducted to understand the interaction of syringin with the molecular mediators involved in the multifaceted interplay in angiogenesis. The anti-angiogenic activity of syringin was evaluated through the chorioallantoic membrane (CAM) assay and the probable molecular targets of the title compound were identified using the reverse docking technique.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1e], Agelasine F is found to display cytotoxicity against a variety of cancer cell lines[1e], [3d] and microorganisms[1e], [2a], including profound activity against Mycobacterium tuberculosis . [3b] A reverse docking study has revealed mycobacterial enoyl reductase and 7,8‐diaminopelargonic acid synthase as a possible enzyme target, but generally the mechanism(s) of action for agelasines are poorly understood. Racemic agelasine F ( 6 ) was synthesized ca.…”
Section: Introductionmentioning
confidence: 99%
“…We have applied CADDD approaches in discovering possible leads against druggable targets in Mtb . 8 17 An interesting drug target in Mtb is the enzyme 7,8-diaminopelargonic acid (DAPA) aminotransferase, more commonly known as Mtb BioA. BioA is involved in biotin biosynthesis pathway, one of the most important survival pathways of Mtb .…”
Section: Introductionmentioning
confidence: 99%